Readout electronics for multichannel detectors - Kulibaba, V.I.; Maslov, N.I.; Naumov, S.V.; Ovchinnik, V.D.; Prokhorets, I.M. (Вопросы атомной науки и техники, 2001)
Readout electronics based on the 128-channel chip “Viking” (IDE AS inc., Norway) is considered. The chip “Viking” integrates 128 low noise charge-sensitive preamplifiers with tunable CR-(RC)² shapers, analog memory and multiplexed readout to one output. All modules of readout electronics were designed and produced in KIPT taking into account the published recommendations of IDE AS inc.